Kesejahteraan SDM sebagai Penentu Kinerja UMKM Ekonomi Kreatif - Amelia, Velanda Ariska (Shofanah Media Berkah, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the creative economy play a crucial role in promoting economic growth and generating employment opportunities. However, the success of small and medium enterprises (SMEs) in enhancing business performance is significantly influenced by the quality and well-being of the human resources (HR) involved. This study aims to examine the role of human resource well-being as a determinant of the performance of creative economy micro, small, and medium enterprises (MSMEs). The research method employed is a Systematic Literature Review (SLR), which examines relevant national scientific journal articles related to the topics of human resource welfare, competence, creativity, innovation, and the performance of small and medium-sized enterprises (SMEs). The SLR process is carried out through the stages of identification, selection, and thematic analysis of literature that meets the inclusion criteria. The results of the study indicate that the well-being of human resources significantly influences the performance improvement of creative economy small and medium enterprises (SMEs), both directly through enhanced motivation and work productivity, and indirectly through the strengthening of competencies, creativity, and innovation. A prosperous HR is generally more adaptable to digitalization and can generate added value that enhances the competitiveness of MSMEs. Nonetheless, there are still several challenges in enhancing the welfare of human resources, such as limited capital, low digital literacy, and insufficient policy support. This study emphasizes that the well-being of human resources is a strategic factor that requires attention in efforts to enhance the performance of creative economy SMEs in a sustainable manner.